Offshore clinical research as a crisis of the ethics of knowledge - Gilberto Corbellini; Alessandra Pietrini (Recenti Progressi in Medicina, 2026)
Summary. The globalisation of clinical research has produced a consolidated system in which trials are progressively relocated to low- and middle-income countries, driven by lower costs, easier recruitment, and reduced regulatory oversight. This structure raises questions that extend beyond participant protection to the epistemic conditions under which biomedical knowledge is produced. The central argument of this paper is that ethical violations in offshore clinical research are not merely parallel to epistemic distortions – they actively generate them through identifiable causal mechanisms. Therapeutic misconception distorts reporting and compliance; coercive enrolment produces artificial adherence and selective dropout; inadequate supervision enables selective reporting of results; insufficient consent generates systematic non-random missing data. Each of these ethical failures is simultaneously a quantifiable methodological confounder. The paper traces the historical dissociation between ethical and epistemic dimensions of research through three phases: an embodied ethos in which methodological and moral integrity were culturally inseparable; a proceduralized ethics from the 1980s onward, in which compliance replaced autonomous evaluation; and a third phase of industrial globalisation in which orientation toward truth lost cultural centrality. The FDA’s 2008 decision to replace the Declaration of Helsinki with GCP-ICH guidelines as the reference standard for foreign trials marks the institutional consolidation of this dissociation. To reconnect the two dimensions, the paper proposes the concept of ethico-epistemic integrity: the coherence between method, social context, and orientation toward objective control. This concept is analytically distinct from research integrity, epistemic justice, and sponsorship bias, and it allows the problem of post-trial access to be reread as a test of the reliability conditions of the research itself. Resolution requires not stricter procedures but cultural change: the reclamation by the physician-investigator of ethical responsibility as a constitutively scientific dimension, including autonomous evaluation of the contextual conditions that determine the epistemic quality of research findings.